IGREJAS DE MISSÃO SEM MISSÃO. ESTUDO DA PRESENÇA PÚBLICA DAS IGREJAS DE MISSÃO ATRAVÉS DAS OBRAS DE SERVIÇO SOCIAL NA CIDADE DE SÃO BERNARDO DO CAMPO - Campos Filho, João Raul de Moura (2012)
The research purpose is to study the public presence of the mission churches - Baptists, Methodists and Presbyterians through the social activities performed in the city of São Bernardo do Campo. The objective is to study how the church in its work effort and mission are accomplishing its social role through the projects performed by institutions legally constituted and active operating. For that the research starts by characterizing historically-socially-economically the region and observing the churches historical antecedents in the city. In a second moment, through the research field, we hope to present how the churches mission formation and development and its social work got started. For last, the research engages in analyzing the social services work related to its contribution for a transforming praxis in the urban scenario. The final considerations from the research is that mission churches has suffered a type of emptiness of action motivated by the actual transformation in the religious field, due to the lack of significative act in the urban context e due to the lack of dialogue and appropriation of the third sector.